A review of virtual-simulation for assessing healthcare students' clinical competency. (January 2021) - Coyne, Elisabeth; Calleja, Pauline; Forster, Elizabeth; Lin, Frances
Abstract: Objectives: Health professional education is transitioning to online platforms to meet students' need for flexibility and international access. However, there is a necessity for authentic presentation of educational material particularly in regard to clinical skills development. There has been major growth in the delivery of virtual simulated-based learning and assessment to provide clinical skill acquisition in an online platform. The aim of this review was to explore the use of virtual simulation to assess clinical competence in health education. Design: Integrative review. Data sources: Peer reviewed studies published between 2008 to March 2020 were searched across PubMed, Embase, Cochrane Library, CINAHL Medline, Scopus, and PsycINFO. Review methods: The Preferred Reporting Items for Systematic reviews and Meta-Analyses was followed. Twenty-three studies, which met the inclusion criteria, were downloaded, and a quality appraisal and analysis was completed by the research team. Results: A thematic analysis identified four themes; pedagogy differences across disciplines, debriefing to enhance learning, preparing healthcare professionals in a safe and cost-effective environment, and managing challenges of virtual simulation. Debriefing with students within the online environment enabled students to share experience and reflect on choices for a deeper learning experience. Conclusions: Virtual simulation can prepare students for the clinical environment by providing safe practice within complex clinical situations. Challenges related to managing and debriefing students must be overcome to ensure best student learning outcomes. Virtual simulation is a feasible strategy to assess students' clinical competency and support their learning in both medical and nursing programs, however simulation should be authentic and incorporate reflection. Highlights: Simulation in medical programs was often task focused, whilst in nursing programs focus was to develop critical thinking Online student debriefing is an important part of the learning process in virtual simulation A virtual world enables students to learn complex clinical reasoning in a safe environment